Helenae encomium - Gorgias (Bibliotheca scriptorum Graecorum et Romanorum Teubneriana., 2016)
Donadi's edition of Gorgias' Helenae encomium takes into account the entire manuscript tradition of this work, offering definitive readings of many obscure passages. The new text goes beyond the schematic distinction between the Ms. Burneianus A and the Ms. X (Palatinus 88) offered by other current editions.